The Influence of Good Corporate Governance on Firm Value with Profitability as an Intervening Variable in LQ45 Companies Listed on The Indonesia Stock Exchange for The Period 2019-2023 - Marissa Deviantara; Isnurhadi Isnurhadi; Marlina Widiyanti; Lukluk Fuadah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to obtain empirical evidence of managerial ownership, institutional ownership, audit committee, and independent board of commissioner and profitability as mediation on the LQ45 Companies value. The sampling technique used purposive sampling, the research samples obtained totaled 19 companies with a research period from 2019-2023 so that there were 95 units of analysis. The research design was quantitative descriptive. The analysis technique in this research is path analysis method. The results showed that Institutional ownership has a significant positive effect on ROA, independent board of commissioner and ROA significant effect on firm's value. The implication of this research is that companies must pay attention to that ROA, independent board of commissioner and Institutional ownership and those that can affect profitabilty and value.